2023
DOI: 10.1063/5.0136564
|View full text |Cite
|
Sign up to set email alerts
|

Scattering characteristics of electrically large arbitrarily shaped targets illuminated by an off-axis vortex electromagnetic beam

Abstract: For the application of vortex electromagnetic (EM) beams in practical detection scenes, the scattering characteristics of electrically large arbitrarily shaped targets illuminated by an off-axis Laguerre–Gaussian (LG) vortex beam are investigated and compared to the on-axis incidence case. The vector potential method is used to extract the electric and magnetic field components of the LG beam in different polarization states. The physical optics algorithm is adopted to calculate the scattering fields of four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The receiving field intensity distributions corresponding to the different polarizations were similar. This conclusion is consistent with the results of previous research [39,41]; that is, for symmetric targets, when the polarization of the receiving field is the same as that of the transmitting field, the topological charge of the scattering field is the same as that of the incident field. When x-linear polarization incidence occurs, other modal components also occupy a portion of the proportion.…”
Section: Ex Ey Ezsupporting
confidence: 93%
See 2 more Smart Citations
“…The receiving field intensity distributions corresponding to the different polarizations were similar. This conclusion is consistent with the results of previous research [39,41]; that is, for symmetric targets, when the polarization of the receiving field is the same as that of the transmitting field, the topological charge of the scattering field is the same as that of the incident field. When x-linear polarization incidence occurs, other modal components also occupy a portion of the proportion.…”
Section: Ex Ey Ezsupporting
confidence: 93%
“…The receiving field intensity distributions corresponding to the different polarizations were similar. This conclusion is consistent with the results of previous research [39,41]; that is, for symmetric targets, when the polarization of the receiving field is the same as that of the transmitting field, the topological charge of the scattering field is Subsequently, the scattering electric field intensity and OAM spectral distribution in the x, y, and z directions of the receiving plane illuminated by vortex EM beams with different polarizations were investigated. The incident frequency was set to 5 GHz, the topological charge was l = 1, and θ 0 = 5 • .The target parameters were consistent with Figure 6.…”
Section: Ex Ey Ezsupporting
confidence: 91%
See 1 more Smart Citation
“…[23] Very recently, it was reported that the off-axis vortex waves illuminate electrically large conductors of different shapes. [24] These results indicate that the OAM spectrum spreading due to inhomogeneous transmission environment will inevitably bring negative influence on the application of vortex beam. However, as a unique feature of vortex electromagnetic wave, the rotating Doppler effect and its application in detecting a rotating target have been studied mostly within the ideal line-of-sight scenarios until now.…”
Section: Introductionmentioning
confidence: 97%
“…[20,21] On the other hand, in the radio frequency range, the transmission of vortex electromagnetic wave is more obviously affected by the scattering of obstacles. [22][23][24] The scattering of high-order Bessel vortex electromagnetic waves on dielectric spheres was studied. [22] Fortunately, the OAM spectrum maintains well after the vortex electromagnetic wave has transmitted through conductor sphere and cone.…”
Section: Introductionmentioning
confidence: 99%